Effects of Aerobic Training Combined with Green Tea Extract on Leukocyte Telomere Length, Quality of Life and Body Composition in Elderly Women - F Hovanloo; H Fallah Huseini; M Hedayati; M Teimourian (Institue of Medicinal Plants, ACECR, 2016)
Background: Exercise and consumption of green tea affect the aging process. However, the effect of exercise training combined with green tea extract on leukocyte telomere length, quality of life (QoL) and body composition in aging has so far been unclear and inconsistent. Objective: The aim of the present study was to determine the effectiveness of aerobic training intervention and green tea extracts consumption either alone or in combination on leukocyte telomere length, QoL and body composition among elderly women. Methods: Thirty six elderly women, 60-65 years, were randomly divided into two groups, the exercise alone (placebo group) and exercise with green tea consumption (green tea group). All participants in both groups were engaged to aerobic protocol exercise three times in week for five months. The participants in green tea group received green tea extract capsule 500 mg and placebo group received toasted powder capsule 500 mg three times a day for a period of five months. At baseline and end of the study the leukocyte telomere length, QoL and body composition were measured. Results: There were significant increase on leukocyte telomere length in green tea group compared with the baseline (P=0.004) and also placebo group (P=0.041) at the end of the study. Waist-hip ratio was also significantly decreased in green tea group compared with placebo group (P=0.016). Conclusion: Our findings shows that combination of aerobic training with consumption of green tea has synergic effect on waist-hip ratio and leukocyte telomere length associated with aging among elderly women.